Living values activities for children ages 8-14 - Tillman, Diane; Liddle, Ruth (Florida : Health Communicatins, Inc, 2000)
Suitable for children aged 8-14, this work offers goals, objectives and detailed lesson plans that explore twelve key units: Peace, Respect, Love, Tolerance, Honesty, Humility, Cooperation, Happiness, Responsibility, Simplicity, Unity and Freedom.
Keywords: character education -- non-fiction